KEPEMIMPINAN INOVATIF DALAM UPAYA MENINGKATKAN PELAYANAN PUBLIKDI KECAMATAN KOTA SUMENEP - Ghufrony, Ahmad; Kadarisman, Kadarisman (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2018)
Inovatif behaviour is often related to creativities. Both of it is true, butbehavioral construct of creativity and inovatif have various difference. Its impactalmost at all of life area, do not aside from governance sector and also of publicorganisation applied by a leader specially District of Town of Sumenep. Focus ofthis research which will reach that is